If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -1 = 8x + -4 Reorder the terms: -1 + 5x = 8x + -4 Reorder the terms: -1 + 5x = -4 + 8x Solving -1 + 5x = -4 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -1 + 5x + -8x = -4 + 8x + -8x Combine like terms: 5x + -8x = -3x -1 + -3x = -4 + 8x + -8x Combine like terms: 8x + -8x = 0 -1 + -3x = -4 + 0 -1 + -3x = -4 Add '1' to each side of the equation. -1 + 1 + -3x = -4 + 1 Combine like terms: -1 + 1 = 0 0 + -3x = -4 + 1 -3x = -4 + 1 Combine like terms: -4 + 1 = -3 -3x = -3 Divide each side by '-3'. x = 1 Simplifying x = 1
| 4(6x+8)=56 | | m=n+14 | | 3x+x+2=4 | | 6+5w+2w=13 | | 2.25x+2=12 | | 2a+13-a=10 | | (x-10)=3 | | 4x-7+1y-7x-[-3y]= | | -10+x+4=7x | | -1x+8+6x-4y-8x+3= | | 12x=8x-4 | | (x)+1=7 | | abs(3-6x)=10 | | 3x(5x-6)= | | 4567r-(56+7895)=-6754 | | 41-u=22 | | 3/4*2=y | | w+9w= | | x+(x*.08)=4900 | | 16=4k | | 3(2x-5)=4x+7 | | 1.2z+1.152=30.6 | | 4(x-7)(x-8)(x+7)=0 | | 12+3y-8+4y= | | 0.5x+5.4=8.6 | | 0=x^2+0-67 | | -3(x-3)=21 | | 5p+24.2=28.65 | | x+1.4x=500 | | -x-9=13-3x | | 0.45x+0.6=0.6x | | 4lnx=3 |